Desertification in the Drylands: A Review of the African Situation - Darkoh, M B K (Annals of Arid Zone, 2016)
Desertification is best conceived as land degradation in drylands. It is a process of sustained decline of the biological productivity of dry lands; the end result is a desert, or skeletal soil that is irrecuperable. The term has raised considerable debate in the literature, and there is little purpose served in the post-UNCED era in expending further energy debating the definition and concept independently from land degradation in general. Enough is now known to conclude that the desertification problem is not a myth and that it is an extremely complex and intractable problem, affecting 3.6 billion hectares of the world’s 5.2 billion hectares of drylands and some 900 million people (about 20% of the world’s population). The nature and causes will be particular to any given situation, depending on the natural ecosystem variables and history of land use. Desertification is normally a very slow process and thus can be assessed Â·over decades of observation, not years. In so far as Africa is concerned, although there are clearly areas of land tbat have become degraded, establishing the extent and trends is not easy. The failure to stanoardise what is being measured and the lack of widespread unambiguous measures has made monitoring difficult and often unreliable. This paper provides a snapshot of desertification in the drylands of Africa. It is contended that desertification in the drylands of .Africa is a complex and multifaceted problem which appears to be caused by climate and human mismanagement of the environment. The principal focus of this paper is therefore a review of the current status of dry land degradation (desertification) and its main causes, i.e. the natural and human disabling factors. The paper also highlights the consequences of desertification and the efforts to combat the problem in .